COMMUNITY BEHAVIOR REGARDING USE OF LATERIES FAMILIES IN THE WORKING AREA OF PANEI TONGAH PUSKESMAS PANEIKA DISTRICT, SIMALUNGUN REGENCY YEAR 2020 - Sidabutar, Sondang; Zhou, Weihuan; Yunardi, Yunardi; Sihombang, Eka; Nurmala, Nurmala (Universitas Efarina, 2021)
One of the goals of health development is to increase healthy living behavior and a healthy environment. This study aims to obtain an overview of community behavior which includes knowledge, attitudes and community actions regarding the use of family latrines in the Working Area of the Panei Tongah Health Center, Panei District, Simalungun Regency which was carried out in July - September 2020. The type of research is a descriptive survey research with an observational approach. The population in this study included all households in the working area of the Panei Tongah Community Health Center, Panei District, totaling 6939 families and spread over 17 sub-districts/ villages namely Panei Tongah Village, Bah Bolon Tongah Village, Simpang Raya Dasma Village, Simpang Raya Village, Mekar Sari Raya Village, Sipoldas Village, Bangun Dasmariah Village, Bangun Rakyat Village, Bangun Sitolubah Village, Simantin Pane Dame Village, Sigodang Village, West Sigodang Village, Rawang Pardomuan Nauli Village, Janggir Leto Village, Siborna Village, NauliBaru Village, Bahliran Siborna Village. So the number of samples in this study were 378 families. Sampling was done randomly. The sampling technique in this study used the proportionate random sampling method, which aims so that the sample can represent all sub-districts/villages in the Working Area of the Panei Tongah Health Center, Simalungun Regency. 8% lack knowledge. Then the attitude of the respondents regarding the use of the new latrine was 71.7% who had a good attitude while 28.3% had a bad attitude. 68.5% of respondents' actions regarding the use of family latrines had positive actions while 31.5% had negative actions. Respondents who used family latrines were only 44.7% and 55.3% did not have latrines. Respondents who used family latrines were 37.3% while those who did not used latrines were 62.7%. So that intensive counseling and coaching is needed that is adjusted to the level of knowledge possessed by respondents, both as a group and individually in order to increase efforts to implement appropriate community attitudes and actions regarding the use of family latrines.